PENGARUH PROFESIONALISME TERHADAP PRESTASI KERJA DOSEN PADA POLITEKNIK LP3I JAKARTA - Eka Putri Handayani; Resti Yulistria; Hasta Herlan Asymar (Jurnal Akrab Juara, 2018)
This research was conducted to obtain the influence of the independent variable profesinalism with work performance he got from his lecturers as dependent variable by taking 60 sample in the population lp3i polytechnic he got from his lecturers jakarta ciledug campus campus blok m which consisted of 60 the people who had given its input through the questionnaire provided researchers and measured by likert scale use correlation polytechnic and regression to hypothesis .The result analysis of the data and test hypotheses are ( 1 ) the value a sig . With 2-tailed 0.787 as much as to the level of a very streght mean so much smaller than the level of significant(Î±) 1 % and value of r2 or coefficient of determination as much as 0.620 , so it can be concluded that h1 accepted which means hypothesis advanced by tested that the impact of which is between the profesionalism with work performance he got from his lecturers .The conclusion of this research is competence , having significant influence with work performance he got from his lecturers in jakarta lp3i polytechnic . Key words: profesinalisme, and work performance.